Lower limb dynamics vary in shod runners who acutely transition to barefoot running. Issue 2 (25th January 2016) - Hashish, Rami; Samarawickrame, Sachithra D.; Powers, Christopher M.; Salem, George J.
Abstract: Relative to traditional shod rear-foot strike (RFS) running, habituated barefoot running is associated with a forefoot-strike (FFS) and lower loading rates. Accordingly, barefoot running has been purported to reduce lower-extremity injury risk. Investigations, however, indicate that novice barefoot runners may not innately adopt a FFS. Therefore, the purpose of this study was to examine lower-extremity dynamics of habitually shod runners who acutely transition to barefoot running. 22 recreational RFS runners were included in this investigation. This laboratory controlled study consisted of two visits one-week apart, examining habitually shod, then novice barefoot running. Foot-strike patterns and loading rates were determined using motion analysis and force plates, and joint energy absorption was calculated using inverse dynamics. Of the 22 runners, 8 maintained a RFS, 9 adopted a MFS, and 5 adopted a FFS during novice barefoot running. All runners demonstrated a reduction in knee energy absorption when running barefoot; MFS and FFS runners also demonstrated a significant increase in ankle energy absorption. Runners who maintained a RFS presented with loading rates significantly higher than traditional shoe running, whereas FFS runners demonstrated a significant reduction in loading rate. Mid-foot strikers did not demonstrate a significant change in loading rate. These results indicate that habitually shod RFS runners demonstrate a variety of foot-strike and lower-extremity dynamic responses during the acute transition to barefoot running. Accordingly, explicit instruction regarding foot-strike patterns may be necessary if transitioning to barefoot. Long-term prospective studies are required in order to determine the influence of FFS barefoot running on injury rates.